Study the Effect of H2S on the Gas-shift Conversion - Sharifian, Seyedmehdi; Abbasian, Saeid; Katal, Reza (Asian Journal of Chemistry, 2011)
The characteristics of conversion of carbon monoxide and hydrogen generation from a water gas shift reaction are investigated experimentally. The behaviour of catalyst (Fe-Cr) was examined with and without the presence of H2S in the feed. With the effect of the high temperature catalyst, increasing reaction temperature will promote the performance of the water gas shift reaction. These behaviours reveal that the water gas shift reaction with the high temperature catalyst is governed by chemical kinetics. It is of interest that water decomposition also develops in the water gas shift reaction so that the concentration of H2 is always higher than that of CO2.